Odpowiedzi

2010-03-23T21:13:11+01:00
-3x=2x-10
-3x-2x=-10
-5x=-10
x=2

2x-2=7-x
3x=9
x=3

10=4-2x
2x=-6
x=-3

-(2x-1)=4
-2x+1=4
-2x=3
x=- 3/2

2(x+1)=x
2x+2=x
x=-2

2t-(3t+1)=6
2t-3t-1=6
-t=7
t=-7

-(4+x)=2(3-x)
-4-x=6-2x
x=10

3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y=2y
0=0

(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=20
x=-4
2010-03-23T21:16:13+01:00
-3x=2x-10
-3x-2x=10
-5x=10 |:(-5)
x=2

2x-2=7-x
2x+x=7+2
3x=9 |:3
x=3

10=4-2x
2x=4-10
2x=-6 |:2
x=-3

-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 |:(-2)
x=-3/2

2(x+1)=x
2x+2=x
2x-x=-2
x=-2

2t-(3t+1)=6
2t-3t-1=6
-1t=6+1
-t=7 |:(-1)
t=-7

-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0

(x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=3+7+10
-5x=20 |:(-5)
x=-4